2014
DOI: 10.14740/jocmr1841e
|View full text |Cite
|
Sign up to set email alerts
|

Teneligliptin As an Initial Therapy for Newly Diagnosed, Drug Naive Subjects With Type 2 Diabetes

Abstract: BackgroundTeneligliptin is a novel, highly selective dipeptidyl peptidase-4 (DPP-4) inhibitor. The aim of this study is to explore the glycemic and non-glycemic efficacies of teneligliptin as an initial therapy.MethodsNewly diagnosed, drug naive Japanese subjects with type 2 diabetes (T2DM) were assigned to 20 mg/day teneligliptin monotherapy (n = 31). At 3 months, levels of glycemic and other parameters were compared with those at baseline.ResultsSignificant reductions of HbA1c (from 10.34 ± 2.06 to 8.38 ± 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…Teneligliptin is a novel DPP-4 inhibitor, having a unique chemical structure which is characterized by five consecutive rings (J-shaped), which might account for its unique potency and half-life time 5,6. Teneligliptin was introduced in India in May 2015 and is available at almost one quarter to one fifth of the cost of other DPP-4 inhibitors (namely sitagliptin, vildagliptin, saxagliptin, and linagliptin).…”
Section: Introductionmentioning
confidence: 99%
“…Teneligliptin is a novel DPP-4 inhibitor, having a unique chemical structure which is characterized by five consecutive rings (J-shaped), which might account for its unique potency and half-life time 5,6. Teneligliptin was introduced in India in May 2015 and is available at almost one quarter to one fifth of the cost of other DPP-4 inhibitors (namely sitagliptin, vildagliptin, saxagliptin, and linagliptin).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, incretin-related agents such as DPP- Teneligliptin which inhibits the enzyme DPP-4 and degrades incretin, a hormone which adjusts blood glucose level and improves blood glucose control as stated above. A survey of chemical literature has shown that the drug Teneligliptin is effectively used to treat Type 2 diabetes mellitus [1][2][3][4][5][6][7][8] (T2DM). Further it is noticed that only a very few methods on the development and validation for the estimation of Teneligliptin are reported which include UV spectrophotometric methods [9][10] and High Performance Thin Layer Chromatographic (HPTLC) method [11] and High Performance Liquid Chromatography (HPLC) methods.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…There were no hypoglycaemic symptoms or serious adverse events. [14] studied the effect of Teneligliptin 20 mg/day as an initial therapy in 31 newly diagnosed type 2 diabetes patients mean age 58.29 ± 14.95 for 3 months. Significant reductions in HbA1c (from 10.34 ± 2.06 to 8.38 ± 2.23%; p < 0.00001) and fasting blood glucose (from 211.3 ± 68.4 to 167.3 ± 70.2 mg/dL; p < 0.0002) levels were observed without any clinically significant adverse events.…”
Section: Hours Glucose Controlmentioning
confidence: 99%